Tuberculosis in Children and Adolescents: Progress and Perseverance - Stephen M. Graham; Ben J. Marais; Farhana Amanullah (Pathogens, 2022)
Although it is an ancient pathogen, tuberculosis (TB) remains a major infectious cause of death globally, transiently displaced by COVID-19 [...]